Dinamika Penyebaran Radikalisme di Pulau Lombok: Faktor Penyebab, Dampak Sosial, dan Upaya Penanggulangannya - Mahmuluddin; Husni, Valencia; Wahyudin, Y.A. (Sosiosaintika, 2025)
The phenomenon of radicalism has become a tangible reality in Lombok Island, marked by the growing exposure of extremist ideologies within its culturally and religiously diverse society. This condition poses a serious threat to social stability and national security, as it disrupts communal harmony and risks triggering horizontal conflicts. This study aims to examine the dynamics of radicalism dissemination in Lombok, identify the key contributing factors that drive extremism and terrorism, analyze the resulting social impacts, and formulate effective and sustainable counter-strategies. Employing a qualitative approach with a case study design, the research utilizes document analysis and relevant secondary data. Findings reveal that the spread of radicalism in Lombok is influenced by community interactions, peer environments, religious figures, and social media platforms, particularly video-based applications such as YouTube. The social impacts include stigmatization of regions and communities, disruption of educational and religious institutions, social and ideological fragmentation, and a decline in tourism and local economic sectors. Countermeasures are carried out through a multi-sectoral approach involving government, civil society, educational institutions, and religious leaders. The main strategies consist of cultural and community-based initiatives, inter-institutional synergy and regulation, deradicalization and counter-radicalism programs, enhancement of digital literacy, and empowerment of deradicalization partners.